Caracterização de queijo tipo camembert fabricado com adição de concentrados lácteos proteicos - Assumpção, Giovana Maria Pereira (2016)
In this work it was evaluated the use of dairy protein concentrate (dpc) in cheese type Camembert, in relation to the manufacturing yields and the influence on the texture profile during maturation and profile of volatile compounds in cheese with 24 days maturation. It was evaluated the role of stirring or not of the cheese mass, in yeld, texture profile and volatile compounds. Two whey protein concentrate, and two milk protein were used. It was estimated the cost by the quantity raw materials used and technological coadjuvants in each treatment to process one kg of cheese. The experimental design was completely randomized. In the evaluation of stirring or not of the mass at time zero it was used the split plot treatments and in the cheese production over time. It was used the schema plot sub-sub-divided on time. The experiments were performed in three replications. The milk characterization was evaluated in relation to its average values. The cheeses‟ chemical composition with and without stirring in a manufacture day; loss of fat and protein in whey; g/L coefficient; yield in L/kg and L/kg adjusted; they were subjected to variance analysis and when significant Tukey test at 5% probability. The data evaluated over time, it was applied to variance analysis and when significant Tukey test at 5% of probability and Regression, when possible. The addition of different dpc to the milk, in cheese production promoted no significant difference in yeld, did not influence in isolation way in the composition, pH and in cheeses‟ proteolysis; promoted less loss of protein in the whey in treatments with addition of milk protein compared to whey proteins, did not influence in isolation way in the fat loss in the whey, in transfer of solids and texture profile, promoted variation in volatile compounds profile. The mechanical work performed or not with the mass, did not promoted significant difference in the yield, it influenced in isolation way in the cheese fat content, presenting the treatments without stirring the highest values, did not influenced in isolation way in the fat loss in the whey, pH and in proteolysis no difference in the loss of proteins in whey, or in the end use of solid, stirring or not the mass, alter the texture profile compared to the control cheese, reducing the adhesiveness with stirring (WS), the elasticity (WS and WOS) and resilience without stirring (WOS) and increased cohesiveness and chewiness (WS and WOS) did not alter the adhesiveness (WOS), varying the volatile compounds profile. Considering the minor: milk fermentation time, loss of protein and fat in whey and that there is no statistically significant difference in fat loss in whey without stirring mass, the use of dpc M1 and M2 stood out among the others. The stirring or not of the mass does not influence the manufacturing yield; it is suggested that the fabrications are carried out without stirring, reducing 30 to 40 minutes the manufacture time.